2011
DOI: 10.1007/s10815-011-9644-3
|View full text |Cite
|
Sign up to set email alerts
|

Sperm transcriptome profiling in oligozoospermia

Abstract: Purpose Investigate in what extent sperm transcriptome of infertile men is different from that of fertile individuals. Methods Semen samples were collected for determination of sperm parameters as well as for RNA isolation. Gene expression profile was investigated in spermatozoa of 8 infertile and 3 fertile men by microarray analysis using the Affymetrix Chip HG-U133 Plus 2.0. Result(s)We observed up to 33-fold reduction expression of genes involved in spermatogenesis and sperm motility. Furthermore, there is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 33 publications
5
70
0
1
Order By: Relevance
“…Ontological and pathway mapping of these differential transcripts showed that different pathways were disrupted, reflective of the altered semen parameter. These included: abnormal sperm morphology characteristic of teratozoospermia as evidenced by changes in the ubiquitin-proteasome and apoptotic pathways (Platts et al 2007); low sperm motility characteristic of asthenozoospermia as evidenced by changes in the ubiquinone biosynthesis pathway (Jodar et al 2012); and low sperm count characteristic of oligozoospermia as evidenced through changes in DNA repair and oxidative stress regulation (Montjean et al 2012). These results provided insight into the possible pathological mechanisms reflecting the different subtypes of male infertility.…”
Section: Semen Rna Profilementioning
confidence: 99%
“…Ontological and pathway mapping of these differential transcripts showed that different pathways were disrupted, reflective of the altered semen parameter. These included: abnormal sperm morphology characteristic of teratozoospermia as evidenced by changes in the ubiquitin-proteasome and apoptotic pathways (Platts et al 2007); low sperm motility characteristic of asthenozoospermia as evidenced by changes in the ubiquinone biosynthesis pathway (Jodar et al 2012); and low sperm count characteristic of oligozoospermia as evidenced through changes in DNA repair and oxidative stress regulation (Montjean et al 2012). These results provided insight into the possible pathological mechanisms reflecting the different subtypes of male infertility.…”
Section: Semen Rna Profilementioning
confidence: 99%
“…The global analysis of spermatozoal mRNAs using microarray technologies greatly contributed to the understanding of mRNA complexity in mature spermatozoa, and has revealed specific mRNA patterns that correlate with male fertility and infertility (52)(53)(54)(55)(56), teratozoospermia (57), smoking (58), and cryptorchidism effects (59).…”
Section: Spermatozoal Rnas As Clinical Markers Of Male Infertilitymentioning
confidence: 99%
“…Male infertility mainly results from azoospermia or oligospermia [Filipponi and Feil 2009], primarily from Y chromosome microdeletions [Sadeghi-Nejad and Farrokhi 2009]. Multiple factors are known to impact spermatogenesis, such as environmental disruptors, genetics, testes pathologies, and multivariant lifestyles [Montjean et al 2012]. The interest towards genetic susceptibility factors contributing to male infertility is increasing, However, only a small proportion of the genes and few polymorphisms have been identified in the infertile male [Carrell et al 2006] due to the multifactorial nature of male infertility.…”
Section: Introductionmentioning
confidence: 99%